The Influence of Financial Literacy and Parents' Income on Saving Behavior Based on Parents' Education and School Status - Prasetyo, Benedictus Singgih; Yulianto, Arief; Setyadharma, Andryan (Universitas Negeri Semarang, 2021)
Saving is an important thing in financial management. However, on the other hand, people's saving behavior, especially teenagers, is still low. The purpose of this study is to determine the effect of financial literacy and parents’ income on students’ saving behavior based on parents’ education and school status in Senior High School of Semarang City. This study used a quantitative approach. The population in this study were the students of class XI Social Sciences of Senior High School in Semarang City which had a good category in the National Examination 2019. The technique of data collection used questionnaire. The data analysis techniques used descriptive and inferential. The result of this study concludes that there are effects of financial literacy and parents' income on saving behavior. However, based on parents’ education, there is no difference in saving behavior. In line with this, if based on school status, there is no difference in students' saving behavior.